Forecasts Marine Weather on Java Sea Using Hybrid Methods: TS-ANFIS - Deasy Alfiah Adyanti; Ahmad Hanif Asyhar; ian Candra Rini Novitasari; Ahmad Lubab; Moh. Hafiyusholeh (IAES Indonesia Section, 2017)
Indonesia is an archipelago. Consequently, themajorities are working around the sea such as a fisherman.While the number of activities at sea are increasing more accident occurred are rising. This research presents marine weather prediction system using Hybrid Methods TS-ANFIS(Adaptive Neuro Fuzzy Inference System – Time Series) in orderto anticipate bad weather and reduce risk. This method use bothocean current and wave height at Java Sea particularly on Gresikin order to forecast ocean current velocity and wave height. Inputvariables used in this paper are data at (t), an hour before (t-1),and two hours before (t-2) and obtained next hour, next 6 hours,next 12 hours, and next day prediction as output. The resultsindicate that ocean current speed attain 16.97327 cm/s; 13.22302cm/s; 10.21107 cm/s; 14.09871 cm/s with mean error is about0.12993; 1.5758; 1.3182; 0.82613 while wave height reach 0.45554m; 0.48286 m; 0.46395 m; 0.54571 m with mean error is about0.0012247; 0.018619; 0.046584; 0.060206. Therefore, it was safe tosailing on 1st January 2016.